Defying the oxidative-addition prerequisite in cross-coupling through artful single-atom catalysts - Jiwei Shi; Gang Wang; Duanshuai Tian; Xiao Hai; Rongwei Meng; Yifan Xu; Yu Teng; Lu Ma; Shibo Xi; Youqing Yang; Xin Zhou; Xingjie Fu; et al. (Nature Communications)
Abstract Heterogeneous single-atom catalysts (SACs) have gained significant attention for their maximized atom utilization and well-defined active sites, but they often struggle with multi-stage organic cross-coupling reactions due to limited coordination space and reactivity. Here, we report an “anchoring-borrowing” strategy combined facet engineering to develop artful single-atom catalysts (ASACs) through anchoring foreign single atoms onto specific facets of the non-innocent reducible carriers. ASACs exhibit adaptive coordination, effectively bypassing the oxidative-addition prerequisite for bivalent elevation at a single metal site in both homogenous and heterogeneous cross-couplings. For example, Pd1-CeO2(110) ASAC exhibits unparalleled activity in coupling with more accessible aryl chlorides, and challenging heterocycles, outperforming traditional catalysts with a remarkable turnover number of 45,327,037. Mechanistic studies reveal that ASACs leverage dynamic structural changes, with reducible carriers acting as electron reservoirs, significantly lowering reaction barriers. Furthermore, ASACs enable efficient synthesis of biologically significant compounds, drug intermediates, and active pharmaceutical ingredients (APIs) through a scalable high-speed circulated flow synthesis, underscoring great potential for sustainable fine chemical manufacturing.